Review Essay: Unravelling Democracy’s Anti-Democratic Machine - Nick Couldry (Journal of Digital Social Research)
This review of two recent books, with further discussion of a third, addresses questions of the direction of democracy and the impacts of media circulation and data extraction on democratic culture. The reviewed books are Selena Nemorin (2018). Biosurveillance in New Media Marketing: World, Discourse, Representation, and Dipankar Sinha (2018). The Information Game in Democracy, with discussion also of Peter Csigo (2016). The Neopopular Bubble: Speculating on “the People” in Late Modern Democracy.